Determination of moisture, total available and soluble extract in spent grains: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Castañé, F. X. (BrewingScience, 1997)
The methods for the determination of moisture, total available and soluble extracts in spent grains have been collaboratively tested by members of the Analysis Committee of the European Brewery Convention to obtain repeatability (r₉₅) and reproducibility (R₉₅) values. Repeatability and reproducibility values of 0.1 and 0.67 respectively were obtained for spent grain moisture’s ranging between 4 and 8% m/m in pre-dried and premilled samples. In a pre-dried and unmilled sample containing 3.4% m/m moisture the values obtained were 0.3 and 1.5 respectively. For total available extract (MEBAK) these values were 0.5 and (2.2+0.045m) respectiveley, with total available extract ranging from 9 to 42% m/m dry matter, where m refers to the actual value. The values for the pre-dried and unmilled sample containing an extract of 41.2% m/m were 0.5 and 4.6 respectively. The precision values for soluble extract werde dependent on the extract level of the sample over the range 6 to 40% m/m dry matter. A repeatability value of 0.13+0.007m and a reproducibility value of 0.2+0.06m were obtained over this range. Values for the same pre-dried and unmilled sample with a soluble extract of 38.7% m/m were 1.3 and 3.8% m/m respectively.